KAJIAN ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI DALAM MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE DALAM PEMBELAJARAN BAHASA - Niswatul Ulya; Rani Setiawaty; Sabrina Putri` Syahada; Laila Nabila; Nehayatul Afdhila Rizqiya Putri (Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes the Value Clarification Technique (VCT) method in Indonesian language learning through ontological, epistemological, and axiological perspectives. Using a Systematic Literature Review (SLR) approach to 12 national journal articles, the study results show: (1) Ontologically, VCT views values ​​as an educational reality that can be developed; (2) Epistemologically, VCT emphasizes critical thinking processes and conscious decision-making; (3) Axiologically, VCT has a positive impact on the formation of character, empathy, and emotional involvement of students. It is concluded that the VCT model is effective in internalizing noble values ​​through reflective, meaningful, and communicative learning.